The costs of creatinine testing in the context of a HIV pre-xxposure prophylaxis demonstration project in Eswatini - Kohler, Stefan; Ndungwani, Rumbidzai; Burgert, Mark; Sibandze, Dumile; Matse, Sindy; Hettema, Anita (Aids and behavior, 2022)
HIV treatment and prevention as well as other chronic disease care can require regular kidney function assessment based on a creatinine test. To assess the costs of creatinine testing in a public health care system, we conducted activity-based costing during a HIV pre-exposure prophylaxis (PrEP) demonstration project in the Hhohho region of Eswatini. Resource use was assessed by a laboratory technician and valued with government procurement prices, public sector salaries, and own cost estimates. Obtaining a blood sample in a clinic and performing a creatinine test in a high-throughput referral laboratory (> 660,000 blood tests, including > 120,000 creatinine tests, in 2018) were estimated to have cost, on average, $1.98 in 2018. Per test, $1.95 were variable costs ($1.38 personnel, ¢39 consumables, and ¢18 other costs) and ¢2.6 were allocated semi-fixed costs (¢1.1 laboratory equipment, ¢0.85 other, ¢0.45 consumables, and ¢1.3 personnel costs). Simulating different utilization of the laboratory indicated that semi-fixed costs of the laboratory (e.g., equipment purchase or daily calibration of the chemistry analyzer) contributed less than variable costs (e.g., per-test personnel time and test reagents) to the average creatinine test cost when certain minimum test numbers can be maintained. Our findings suggest, first, lower creatinine testing costs than previously used in cost and cost-effectiveness analyses of HIV services and, second, that investment in laboratory equipment imposed a relatively small additional cost on each performed test in the high-throughput referral laboratory.
Online veröffentlicht: 18. August 2021
Gesehen am 12.06.2023